All slums are not equal: Maternal health conditions among two urban slum dwellers - Zulfia Khan; Saira Mehnaz; Abdul Razzaq Siddiqui; Athar Ansari; Salman Khalil; Sandeep Sachdeva (Wolters Kluwer Medknow Publications, 2012)
Background: Pregnant women inhabiting urban slums are a "high risk" group with limited access to health facilities. Hazardous maternal health practices are rampant in slum areas. Barriers to utilization of health services are well documented. Slums in the same city may differ from one another in their health indicators and service utilization rates. The study examines whether hazardous maternal care practices exist in and whether there are differences in the utilization rates of health services in two different slums. Materials and Methods: A cross-sectional study was carried out in two urban slums of Aligarh city (Uttar Pradesh, India). House-to-house survey was conducted and 200 mothers having live births in the study period were interviewed. The outcome measures were utilization of antenatal care, natal care, postnatal care, and early infant feeding practices. Rates of hazardous health practices and reasons for these practices were elicited. Results: Hazardous maternal health practices were common. At least one antenatal visit was accepted by a little more than half the mothers, but delivery was predominantly home based carried out under unsafe conditions. Important barriers to utilization included family tradition, financial constraints, and rude behavior of health personnel in hospitals. Significant differences existed between the two slums. Conclusion: The fact that barriers to utilization at a local level may differ significantly between slums must be recognized, identified, and addressed in the district level planning for health. Empowerment of slum communities as one of the stakeholders can lend them a stronger voice and help improve access to services.